The Efficacy of a Group Cognitive Behavioral Therapy for War-Affected Young Migrants Living in Australia: A Cluster Randomized Controlled Trial - Ooi, Chew S.; Rooney, Rosanna M.; Roberts, Clare; Kane, Robert T.; Wright, Bernadette; Chatzisarantis, Nikos (Frontiers in Psychology, 2016)
Background Preventative and treatment programmes for people at risk of developing psychological problems after exposure to war trauma have mushroomed in the last decade. However, there is still much contention about evidence-based and culturally sensitive interventions for children. The aim of this study was to examine the efficacy of the Teaching Recovery Techniques in improving the emotional and behavioural outcomes of war-affected children resettled in Australia. Methods and findings A cluster randomised controlled trial with pretest, posttest, and 3-month follow-up design was employed. A total of 82 participants (aged 10 to 17 years) were randomised by school into the 8-week intervention (n = 45) or the waiting list (WL) control condition (n = 37). Study outcomes included symptoms of posttraumatic stress disorder, depression, internalising and externalising problems, as well as psychosocial functioning. A medium intervention effect was found for depression symptoms. Participants in the intervention condition experienced a greater symptom reduction than participants in the WL control condition, F(1,155) = 5.20, p = .024, partial ƞ2 = 0.07. This improvement was maintained at the 3-month follow-up, F(2,122) = 7.24, p = .001, partial ƞ2 = 0.20. Conclusions These findings suggest the potential benefit of the school and group-based intervention on depression symptoms but not on other outcomes, when compared to a waiting list control group. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12611000948998